PENGARUH LABA BERSIH, ARUS KAS OPERASI, LEVERAGE DAN DIVIDEN TAHUN SEBELUMNYA TERHADAP DIVIDEN TUNAI (Studi Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2010-2013) (Proceeding SENDI_U, 2015)
The decision to determine how much of the dividend to be distributed to investors guided by how much money thecompany. Net income, operating cash flow, and leverage may explain the company's financial condition. Payment ofdividend the previous year also can explain the dividend payment for the year. This research aims at analyzing the effectof net margin, operating cash flow, leverage, and dividend payment of previous year to cash dividend. The populationof this research was all of companies that have been included into classification of go public manufacturing industriesand the companies have been administered at BEI from 2010 until 2013. The technique of sampling used was purposivesampling. After collecting the companies appropriate with the category, it was obtained the sample was 21. Because theresearch had been done four years, total of observation was 84. The technique of analysis used was multiple regression.The result of this research proved that net margin, operating cash flow and dividend payment of previous year influencepositively an significantly to cash dividend, while leverage does not influence to cash dividend.Keywords: operating cash flow, cash dividend, net margin, leverage.